Antidiabetic and antilipidemic effect of Ilex kaushue S.Y. Hu (Aquifoliaceae) leaves’ extract on streptozotocin-induced diabetic mice - Nguyen Thi Huyen, Nguyen Thi Thuy, Nguyen Thi Nhung, Phan Hong Minh, Bui Thanh Tung (Journal of Applied Pharmaceutical Science, 2021)
Diabetes disease is a worldwide problem. Until now, there is no effective treatment. Traditional medicine uses Ilex kaushue S.Y. Hu (Aquifoliaceae) for supporting the treatment of diabetes and hyperlipidemia. This study was conducted to evaluate the α-glucosidase inhibitory activity and the hypoglycemic and hypolipidemic effect of I. kaushue leaves’ extract. Ilex kaushue leaves were extracted by ethanol 30% with sonication 45 minutes, which was repeated thrice. Ilex kaushue leaves’ extract was used to evaluate the α-glucosidase inhibitory activity in vitro and the hypoglycemic and hypolipidemic effect in vivo on streptozotocin-induced diabetic mice (50 mg/kg b.w. i.p.). Our results show that I. kaushue leaves’ extract had a moderate α-glucosidase inhibitory activity with an IC50 value of 147.25 μg/ml and strong hypoglycemic and hypolipidemic effect on diabetic mice. Our data show that I. kaushue leaves’ extract has the potential antidiabetic and antilipidemic effect.
Keywords: Ilex kaushue S. Y. Hu, streptozotocin, diabetes, hypoglycemic, hypolipidemic,α-glucosidase.